Efektivitas Ekstrak Etanol Buah Bit (Beta Vulgaris L.) Terhadap Penurunan Glukosa Darah Pada Tikus Model Diabetes - Otniel Agung Ahasyweroz T; Astriani Natalia Br Ginting; Vera Estefania Kaban (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Diabetes is a metabolic disease caused by hyperglycemia, characterized by an increase in blood sugar levels because insulin does not function properly. Beetroot is rich in fiber, minerals such as potassium, sodium, vitamins, and iron which are very beneficial for the body. In addition, this fruit also has bioactives such as betalain, phenolics, and saponins This study aims to determine the effect of giving lily ethanol extract gel in healing wounds in male rat diabetic models. This research method in vivo used induced male rats with an allexone of 120mg/kgBB. Treatment in rats was divided into 6 treatments, namely normal, negative control, positive control EEBB 200mg/KgBB, EEBB 400mg/KgBB, EEBB 600mg/KgBB. This study was conducted for 15 days. The results showed that Beet Ethanol Extract at a dose of 600mg/Kg BB showed the most significant decrease in blood glucose in rats. Doses of 200 and 400 turned out to be almost as effective as metformin tablets. The conclusion obtained is that Beet Fruit Ethanol Extract (Beta vulgaris L.) is effective in lowering blood glucose levels.